Refeeding with Free Lactose Milk ( A1 - 110 Nestle) in Children Suffering from Gastroenteritis and Dehydration - Suharjono, Suharjono; Sunoto, Sunoto; Boediarso, Aswitha; Hendardji, Hentyanto; Soegiharto, Soegiharto (Paediatrica Indonesiana, 2017)
Forty one infants suffering from diarrhoea hospitalized in the Department of Child Health, Medical School, University of lndonesia/Dr. Tjipto Mangunkusumo General Hospital, Jakarta, from August 15, 1973 to January 15, 1974 were refed with "free lactose milk". The result is as follows : 1. From the point of view of increase of body weight: 27 (65.8 %) out of 41 cases were excellent. 2 ( 4.9 %) out of 41 cases were good. 12 (29.3 %) out of 41 cases were poor. 2. From the point of view of stopping the diarrhoea : 25 (60.9 %) out of 41 cases were excellent. 10 (24.5 %) out of 41 was good. 6 (14.6 %) out of 41 cases were poor.